Evaluation of Fire Safety System Implementation in the Rectorate and Lecture Buildings of Universitas Pahlawan - Aniisya, Khairun; Adeswastoto, Hanantatur; Gusman, Deddy (Journal of Engineering Science and Technology Management, 2026)
The results of this study show that the implementation of the fire safety system at Universitas Pahlawan Tuanku Tambusai buildings is considered poor based on the standards of quantity, size, site completeness, means of rescue, and active protection systems. Furthermore, the fire safety reliability system has partially followed applicable SNI (Indonesian National Standard), but some systems have not yet complied with the required safety standards. The methods used in this study include a descriptive method to determine the implementation of rescue facilities and passive protection systems against fire hazards, and a quantitative descriptive method to assess the reliability of building safety systems against fire hazards. Construction in major cities is currently increasing. The construction of various buildings aims to achieve urban success in improving public welfare. One of the safety aspects that must be considered in building construction is safety from fire hazards. The purpose of this study is to determine the implementation of the fire safety system in lecture buildings and to assess the level of fire safety reliability in accordance with the Indonesian National Standard (SNI) in lecture buildings.